Reservoirs Characterization, Compartmentalization, and Modelling on Hydrocarbon Reserve Estimation of A and B Intervals, Keysha Field, Mentawir Formation, Kutai Basin, East Kalimantan Province - Nugroho Wicaksono - Nim: 12013040 , Akbar
Keysha Field is one of the gas fields located in Kutai Basin, East Kalimantan province, with the coordinates of 117,40BT-117,60BT dan 0,40LS-0,90LS. Keysha Fields is a development stage field and has an area about 44,5 km2. The study was conducted at A and B intervals of Keysha Field Deep Zone with total of 72 wells. Objectives of the study are to conduct reservoir characterization, define reservoir compartmentalization, and build three dimensional geological model in estimating gas reserves and discovering actual potential reserves that have not been developed. The methods used consist of facies and stratigraphy sequences analysis, geological modelling, reservoir compartments analysis, and estimation of initial and actual gas reserve. Core description analysis conducted at research’s intervals resulted in 13 lithofacies with facies associations of distributary channel, distributary mouthbar, crevasse splay as reservoirs and prodelta mud, delta front mud, and delta plain mud act as seals. Interpretation on lithofacies and facies associations shows delta depositional environment with northwest – southeast trending of sedimentation. Reservoir quality of distributary channels facies is slightly better than creavasse splays and mouthbars as the ratio of shale’s percentage is higher at the splays and mouthbars. Reservoir heterogenities which contolled by normal fault and facies changes are are also affecting reservoir compartmentalization of the research’s intervals. Integration between reservoir connectivity analysis using pressure data, fluid contact evolution, and sedimetological concepts help in defining reservoir compartmentalization. As the result, 11 regions of hydrocarbon accumulation with significant fluid contacts are identified within research’s intervals. Three dimensional static reservoir modelling consist of structural, facies, and petrophysical modelling were performed in order to determine reservoir geometries, property distributions, and hydrocarbon reserves estimation. Estimated gas reserves from static model are further validated with estimated gas reserves from material balance analysis, thus giving high level of confidence in the interpretation of reservoir geometries, reservoir compartments, and the estimation of gas reserves. From the calculation process, the initial gas in place is 13.7 bcf at intervals A and 48.32 bcf at interval B, as well as the remaining gas in place is 3.18 bcf at intervals A and 20.63 bcf at interval B.